KAJIAN EKONOMI KONSTRUKSI PERKERASAN LENTUR DAN KONSTRUKSI PERKERASAN KAKU (STUDI KASUS JALAN RAYA PKT.EBL-02 TOHPATI - KUSAMBA) - Tri Hary Astuti, Hevie; Adnyana Putera, I G. A.; Putu Suparsa, I G. (JURNAL SPEKTRAN; vol 2, No 1, Januari 2014, 2014)
This study takes the case PKT. EBL highway Tohpati – 02 – Kusamba.The purpose of this study was to conduct economic studies flexible pavement and rigid pavement based on primary data and secondary data obtained from government agencies, the analysis in this study using the methode of costs and benefits. For flexible pavement; assuming traffic growth factor of 3.66%, inflation at 5.68% and the interest rate of 15% / year, 25% / year and 30% / year, and the fluctuating value of IRI. The results obtained for the 15% interest rate per year is NPV = Rp. 98,517,603,656, -, BCR = 1.42; interest rate to 25% per year is NPV = Rp. (65,520,977,844, -), BCR = 0.96; interest rate to 30% per year is NPV = Rp. (69,846,272,752, -), BCR = 0.51, moderate IRR = 24.38%. It can be concluded that the Highway Pavement Bending PKT.EBL-02 Tohpati - Kusamba is economically feasible at the rate of 15% per year with an IRR above. For Rigid Pavement; assuming traffic growth factor of 3.66%, inflation at 5.68% and the interest rate of 15% / year, 25% / year and 30% / year, and the value of IRI stable. The results obtained for the 15% interest rate per year is NPV = Rp. 159 515 604 651, -, BCR = 2.20; interest rate to 25% per year is NPV = Rp. 2068846698, -, BCR = 1.01; interest rate to 30% per year is NPV = Rp. (65,250,533,141, -), BCR = 0.51, moderate IRR = 25.15%. It can be concluded that the Rigid Pavement on Highway-02 PKT.EBL Tohpati - Kusamba is economically feasible at the rate of 15% per annum and 25% per year with an IRR above. In the concluding remarks of the above where rigid pavement IRR greater than the flexible pavement, the results of the economic analysis of this study is that the rigid pavement is more profitable than the flexible pavement.
Keywords: economic study, flexible pavement, rigid pavement